Modest Ag-Extension and Access to Seeds of Aromatic Rice Can Boost Returns of Smallholder Farmers in Uganda, A Case Study - Alibu, Simon; Obura, Morish; Ekebu, James; Nampamya, Doreen; Lamo, Jimmy; Asea, Godfrey; Tae-Seon, Park (Agriculture, 2022)
Limited farmer access to quality seeds of improved varieties and knowledge gaps in good agronomic practices are the major factors limiting rice productivity among smallholder farmers in Uganda. Promoting high yielding aromatic rice varieties alongside good agronomic practices can unlock commercial opportunities for smallholder farmers in rice cultivation, given that 80% of rice consumers in Uganda prefer aromatic rice, which is in short supply. This case study highlights a project’s achievements to accelerate the adoption of improved aromatic rice varieties among smallholder farmers in Uganda. This project supported a few selected farmers with the seed of a new aromatic rice variety, NARORICE-1, and equipped them with agronomic skills to raise their yields from an average of 3.1 to 4.1 t/ha. Line transplanting was identified as a crucial technology to increase rice yields among smallholders. Costly and inaccessible crop-enhancing inputs such as seeds and fertilizers, and an unfair distribution of irrigation water were the two main obstacles farmers face in rice production. Farmers valued NARORICE-1 for its aroma, high yield, and early maturity. The project’s training of a community seed producer improved farmers’ access to NARORICE- 1 seeds, increasing its adoption by 20% in two years. NARORICE-1 is much more in demand than any other variety and attracts a better price, making it an ideal innovation for increasing productivity and farmer’s incomes. An effective seed system and continuous farmer training are vital for accelerating impact.
Keywords: fragrant rice; NARORICE-1; PR-107; Doho rice scheme